Aqueous Synthesis of Cu-doped Zn-based Quantum Dots with Light- Enhanced Cytotoxic Capacity for Potential Biomedical Applications - Bailon-Ruiz, Sonia; Perales-Perez, Oscar (Current Nanoscience, 2016)
Background: Quantum dots are novel nanomaterials with high potential in the biomedical field. Methods: This manuscript reports the direct aqueous synthesis of Cu-doped Zn(Se,S) quantum dots (QDs) via a microwave irradiation-assisted technique. Results: X-ray diffractometry measurements suggested that synthesized nanostructures exhibited a Zn(Se,S) solid solution-like structure with an average crystallite size estimated at 3.6 ± 0.3 nm, which was also corroborated by High-Resolution Transmission Electron Microscopy. Fluorescence measurements of the QDs revealed a green emission peak, centered on 519 nm, that would confirm the actual incorporation of copper species into the Zn(Se,S) host. The toxicity of light-activated QDs was evaluated in cell lines of pancreatic cancer, PANC-1. The viability assay for the PANC-1 control group after 15 minutes of UV exposure was 83% ± 8%. This value went down to 40% ± 7% and 25% ± 2% after contacting the cells with Cu-doped Zn-based QDs, (50 μg/mL), for UV irradiation times of 15 minutes and 60 minutes, respectively. Conclusion: The confirmed capacity of the QDs to generate cytotoxic singlet oxygen species could explain their observed light-enhanced toxicity towards PANC-1. Accordingly, as-synthesized Cu-doped Zn-based QDs can be potentially considered as direct photosensitizers for bio-medical applications.
Keywords: photoluminescence